OP0076 JAK-INHIBITORS TOFACITINIB AND BARICITINIB IMPROVE PATHOLOGICAL BONE LOSS IN VIVO. (June 2019) - Adam, Susanne; Simon, Nils; Steffen, Ulrike; Harre, Née; Andes, Fabian; Müller, Dorothea; Culemann, Stephan; Andreev, Darja; Hahn, Madelaine; Scholtysek, Carina; Schett, Georg; Krönke, Gerhard; et al.
Abstract : Background: Targeting cytokines relevant to rheumatoid arthritis (RA) has proven efficient in clinical practice, but there is still demand for therapies that rebuild joint tissues which have been subjected to deterioration. Since many cytokines involved in RA rely on the intracellular janus kinase - signal transducer and activator of transcription (JAK-STAT) signaling pathway, targeting them presents itself as option. For this approach, JAK-inhibitors such as Tofacitinib and Baricitinib, targeting JAK1/JAK3 and JAK1/JAK2 respectively, seem favorable, as they have been approved for the treatment of RA 1 . Moreover, preliminary data indicates an impact of JAK inhibition on local bone formation. Objectives: To investigate the influence of JAK-inhibition on structural bone damage in vivo and its impact on osteoclast/osteoblast-mediated bone homeostasis in vitro . Methods: In vivo analysis comprised unchallenged steady-state, the ovariectomy-induced mouse model of postmenopausal osteoporosis (OVX) and the serum-induced arthritis (SIA) mouse model. For steady-state analysis C57BL/6 (WT) mice obtained tofacitinib QD by oral gavage for 6 weeks. For OVX, WT mice received tofacitinib BID by oral gavage for 6 weeks. WT mice of the SIA model were fed tofacitinib or baricitinib BID for 14 days. Experimental readout included clinical parameters, ELISA (RANKL/OPG levels in serum), qPCR (mRNA expression in bone) and µCT. For in vitro analysis, murine osteoclasts (OC) were analyzed with TRAP staining (osteoclastogenesis) and von Kossa staining (Resorptive capacity). Murine osteoblasts (OB), derived from mesenchymal stem cells (MSC) and calvariae were assessed with qPCR (differentiation) and Alizarin red staining (mineralization capacity). Results: In steady-state conditions, JAK-inhibition by tofacitinib enhanced tibial trabecular bone density and decreased RANKL/OPG fraction in blood serum. These findings, and increased trabeculae numbers, were also applicable to spinal bone of tofacitinib-treated OVX mice. In SIA, both baricitinib and tofacitinib improved clinical symptoms and halted trabecular and cortical bone loss. In vitro OC-differentiation and function were not affected by JAK-inhibition. However, tofacitinib and baricitinib amplified OCN expression in MSC-derived OBs at day 1 after osteogenic induction, together with reduced Igf1 and elevated Dkk1 levels at day 7. Moreover, as a result of JAK-inhibition RANKL expression was decreased in calvaria-derived OBs. Accordingly, both MSC- and calvaria-derived OBs showed increased mineralization when treated with JAK-inhibitors. Conclusion: Our results suggest that JAK-inhibition by tofacitinib and baricitinib causes increased mineralization by osteoblasts, resulting in enhanced bone density in vivo, in both unchallenged and pathological mouse models. Reference: [1] Baker KF, Isaacs JD, ARD, 2018 Acknowledgement: Work funded by Pfizer, Eli Lilly. The MSC were a kind gift from Farida Djouad (IRMB, Centre Hospitalier Régional Universitaire de Montpellier). Susanne Adam is graduate member of IRTG1181 and Lifa@FAU. Disclosure of Interests: Susanne Adam: None declared, Nils Simon: None declared, Ulrike Steffen (née Harre): None declared, Fabian Andes: None declared, Dorothea Müller: None declared, Stephan Culemann: None declared, Darja Andreev: None declared, Madelaine Hahn: None declared, Carina Scholtysek: None declared, Georg Schett: None declared, Gerhard Krönke Grant/research support from: Lilly, Pfizer, Speakers bureau: Novartis, Silke Frey: None declared, Axel Hueber Grant/research support from: Novartis, Pfizer, Lilly, Consultant for: Lilly, GSK, Novartis, Janssen, Celgene, Abbvie, Roche, Speakers bureau: Lilly, Janssen, Novartis, Celgene, Biogen, Abbvie, BMS